The 17th International Conference on Biomedical Engineering : ICBME 2016, 7th to 10th December 2016, Singapore - Goh, J. C. H. 1955-; Lim, C. T.; Leo, Hwa Liang (Springer, 2017)
This volume presents the proceedings of the 16th ICMBE held from 4th to 7th December 2016, Singapore. Topics of the proceedings include 6 tracks: BioImaging and BioSignals, Bio-Micro/Nano Technologies BioRobotics and Medical Devices, Biomaterials and Regenerative Medicine.- BioMechanics and Mechanobiology., Engineering/Synthetic Biology.
Keywords: Biomedical engineering -- Congresses.; elektronické knihy; electronic books